The impingement factors of quality of life among community who reside near to the rivers - Idris, Khairuddin; Mazuki, Raidah; Md. Yassin, Sulaiman; Hamzah, Azimi; Abu Samah, Asnarulkhadi; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2014)
The main attempt of this study is to identify the factors that impinge the quality of life among community who reside near to Tembeling, Pahang and Muar Rivers. This is a quantitative study where a developed questionnaire was used to collect the data. A total of 240 questionnaires were distributed to the selected respondents in 4 places which is Kg. Jorak (Johore), Kg. Bantal (Pahang), Kg. Gintong (Pahang) and Kg. Langkap (Negeri Sembilan). Although, there is a number of factors that can impinge the quality of life, however within the scope of this study, it focuses on 5 factors that have the potential to influence the quality of life to this community, namely; age, income, period of staying, distance to the nearest river and distance to the nearest city. Analyses performed have confirmed that factors of level of education and areas have significant difference with quality of life while factor of income was detected to have significant relationship with quality of life. A number of discussions have been placed and it is hope that such discussion could assist the relevant parties in constructing concrete strategies to further, uplift the quality of life of the community particularly those who reside near to the river.